Serum cytokine and adhesion molecule profile differs in newly diagnosed acute myeloid and lymphoblastic leukemia - Horáček, Jan; Kupsa, Tomáš; Vašatová, Martina; Jebavý, Ladislav; Žák, Pavel (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2015)
AIMS: To compare serum levels of 17 cytokines and 5 adhesion molecules in patients with newly diagnosed acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL) using biochip array technology. METHODS: A total of 15 AML and 15 ALL patients were studied. Serum samples were taken prior to anticancer therapy and were analyzed by biochip based immunoassays on the Evidence Investigator analyzer. This approach allows simultaneous detection of multiple analytes from a single sample. T-tests were used for statistical analysis. RESULTS: Comparing cytokine and adhesion molecules levels in newly diagnosed AML and ALL patients, we found significant increase in AML in serum IL-4 (P < 0.0001), IL-2 (P < 0.01), IL-3 (P < 0.05), and significant decrease (P < 0.05) in serum VEGF and VCAM-1. DISCUSSION: Our results indicate that serum profile of cytokines and adhesion molecules differs in newly diagnosed AML and ALL patients. Further studies are needed to establish if these alterations could be used as a clinically relevant biomarker for acute leukemias.
Keywords: Young Adult; Cell Adhesion Molecules; Male; mladý dospělý; cytokiny; molekuly buněčné adheze; Adult; Diagnosis, Differential; akutní myeloidní leukemie; dospělí; mužské pohlaví; lidé středního věku; Protein Array Analysis; akutní lymfatická leukemie; lidé; ženské pohlaví; Humans; diferenciální diagnóza; čipová analýza proteinů; Cytokines; Female; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Biomarkers, Tumor; nádorové biomarkery; Leukemia, Myeloid, Acute; Middle Aged